CARDIOVASCULAR PATHOLOGY IN CHILDREN WITH TYPE I MUCOPOLYSACCHARIDOSIS - N. D. Vashakmadze; L. S. Namazova-Baranova; A. K. Gevorkyan; L. M. Kuzenkova; M. A. Babaikina; N. A. Berezneva; T. V. Podkletnova (Union of pediatricians of Russia, 2014)
The article present current published data on the incidence rate, pathogenesis, clinical manifestations, diagnosis and treatment oflife-threatening conditions of the cardiovascular system at type I mucopolysaccharidosis (MPS). Mucopolysaccharidosis is a raregenetically determined disease with chronic progressive course and wide range of clinical manifestations. Specific relevance of thedisease is justified by its severe incapacitating potential, development of a large number of complications of various organs and systems (up to failure), difficulty diagnosing and high risk of fatal outcomes as early as in childhood. Prevalence and severity of cardiovascular disorders in such patients is very high. Currently, there are two methods of treating MPS patients based on pathophysiology of this disease: transplantation of hemopoietic stem cells, which is used only in certain patients, and enzyme-replacement therapy. Early diagnosis and timely launched treatment help to improve condition of patients, attenuate the disease course, including termination of progression of cardiac disorders.